Avian cognition: examples of sophisticated capabilities in space and song. Issue 3 (16th March 2015) - McMillan, Neil; Hahn, Allison H.; Spetch, Marcia L.; Sturdy, Christopher B.
<x xml:space="preserve">Abstract</x> Although birds have traditionally and colloquially been considered less cognitively complex than mammals, and especially primates, more recent research has consistently refuted these assumptions. We argue that the impressive abilities of birds to navigate and communicate require considerable information‐processing capabilities. These capacities include collecting, organizing, and selecting from a wide variety of navigational cues to orient toward and find a goal location in the spatial domain, and utilizing open‐ended categorization and possibly even abstract reasoning to discriminate species‐specific acoustic features of songs and calls. Furthermore, these abilities may be present across many avian species, providing evidence for domain‐general cognitive facilities. We provide examples of processes in spatial learning and communication in birds, and locate them within the general literature, as evidence that the term 'bird‐brain' should not be considered a pejorative. WIREs Cogn Sci 2015, 6:285–297. doi: 10.1002/wcs.1346 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.